Modeling and optimization of a multiple (cascading) phase change material solar storage system. (1st June 2021) - Nekoonam, Saeed; Roshandel, Ramin
Highlights: A cascaded PCM thermal energy storage was optimized connected to a solar air collector. PCM type and channel height are considered as decision variables for optimization. The optimal configuration includes two columns of RT80 and three columns of RT50. PCT of the last stage and enthalpy of the first stage were found very determinative. The optimal stored energy and storage efficiency were improved 6% and 7%. Abstract: Utilization of heat storage units in solar energy systems can resolve the challenge of fluctuation and uncertainty of the solar energy. Phase change materials (PCMs) are used as the storage media for solar energy storage systems. In this research, a system including of a solar collector and a PCM-based cascaded energy storage unit was numerically investigated. Air was used as the heat transfer fluid (HTF) and three paraffin-based materials (RT50, RT65, and RT80) were used as PCM for the energy storage unit. The investigated system mainly operates between 15 °C and 90 °C and considering different PCMs, the selected PCMs were appropriate. Paraffin-based PCMs also present acceptable thermal efficiency and stability regarding the storage application. Developed governing equations were solved using the finite-difference method. The effective heat capacity (EHC) method was integrated into a two-dimensional transient thermal model to determine the temperature distribution within the energy storage unit. The Genetic algorithm (GA) was applied for optimization to achieve the maximum level of stored energy for one entire day. Results showed that phase change temperature (PCT) of the PCM located at the last layer of the cascaded section, is a key element for the level of stored energy. It was observed that the latent heat of phase change (LHPC) is a key factor for the first PCM layer selection (of the cascade). Also, the multiple-PCM energy storage unit at its optimal configuration, improves the charging efficiency of the storage by at least 7%.